Madrasah Management In Improving Teacher Professionals At MTSN I Kerinci - Pirmanuddin, Pirmanuddin; Ali Marzuki Zebua; Yuni Fitri (International Journal of Technology and Education Research, 2023)
Related with with implementation management quality in the environment MTsN I Kerinci, head of the madrasa who became leader in environment Madrasa of course have important role _ in print a professional teacher . Teacher too very determine Where to direction And at a time objective participant educate . As for task headmaster as leader And at a time as a supervisor is obliged help teachers at school For develop profession And at a time help teachers to be able see problem he faces Good in class nor outside class . A must try thought And run To use enhancement quality education is learning process improvement very teaching depends to teacher professionalism as source Power human. Teachers are required For own various Skills in deliver student For reach planned goals. Quality management something institution education seen of inputs include: students, power teachers, administrators, funds, facilities, infrastructure, curriculum, books library And tool learning. Process includes : management institution, management activity Study teaching, interaction academic And other. Results includes: graduates, publications findings scientific and results other .